The Distributional Impact of Serbia’s Taxes and Social Spending - Nguyen, Trang V.; Žarković, Jelena; Vladisavljević, Marko; Ranđelović, Saša (Washington, DC : World Bank, 2022)
In the context of economic recovery and structural reforms to boost Serbia’s living standards, understanding the impact of fiscal policy on inequality and poverty is key to inform policy choices. This paper’s key research question is to analyze the redistributive effect of fiscal policy on income distribution and poverty in Serbia. It advances on the previous literature by comprehensively assessing the individual and combined effects of taxes and social spending on both inequality and poverty in Serbia, using the Commitment to Equity Assessment approach. The findings suggest that Serbia’s fiscal system is redistributive, reducing the Gini coefficient of income once taxes, transfers, and in-kind benefits in education and health are taken into account. However, the inequality-reducing impact of the fiscal system in Serbia is somewhat smaller than what is observed in other countries in Central and Eastern Europe and Latin America, where similar analysis has been applied. Moreover, and like in some other countries in Europe and Central Asia, the fiscal system increases poverty. Direct social transfers in Serbia are pro-poor and inequality reducing, but their impacts are not large enough to fully offset those of taxation since spending on these programs is small. This analysis of fiscal incidence in Serbia provides a useful basis for assessing the impacts of potential changes in taxes or benefits, which can inform options to mitigate short-term adverse impacts and build support for reforms.